Datasonic: Going Public - Mohd Rashid, Rasidah; Murugiah, Logasvathi (2017)
At 8.00 am on January 6, 2012, the Chief Operating Officer (COO) of Datasonic was entering his office which was located at its headquarters in Kuala Lumpur.Raymond, the COO,began looking at all the documents that were placed on his table. All these papers have to be scrutinized and a report prepared before the historic culmination of a new journey. Although Raymond was already exhausted thinking about the numerous events leading to the new chapter of the company, he was adamant about forging ahead. His company was on the verge of pursuing an initial public offering (IPO) and was about to experience a big and important change soon.Just as he was thinking even further, the telephone on his table rang.In fact, the telephone in his office had been ringing incessantly over the past few days.There was an urgency hanging in the air as the telephone rang today. It appears as if Raymond would be unable to reject any calls at all today for it rang so clearly, so loudly and so importantly.As Raymond picked up the mouth piece to speak, he could hear a familiar voice, that of the founder of Datasonic, Datuk Abu Hanifah, who was on the other end.